Correlations between community-level HIV preexposure prophylaxis coverage and individual-level sexual behaviors among United States MSM. (15th November 2022) - Mann, Laura M.; Le Guillou, Adrien; Goodreau, Steven M.; Marcus, Julia L.; Sanchez, Travis; Weiss, Kevin M.; Jenness, Samuel M.
Abstract : Objective: To evaluate if community-level HIV PrEP coverage is correlated with individual sexual behaviors. Design: We used demographic, behavioral, and sexual network data from ARTnet, a 2017–2019 study of United States MSM. Methods: Multivariable regression models with a Bayesian modeling framework were used to estimate associations between area-level PrEP coverage and seven sexual behavior outcomes [number of total, main, and casual male partners (network degree); count of one-time partnerships; consistent condom use in one-time partnerships; and frequency of casual partnership anal sex (total and condomless)], controlling for individual PrEP use. Results: PrEP coverage ranged from 10.3% (Philadelphia) to 38.9% (San Francisco). Total degree was highest in Miami (1.35) and lowest in Denver (0.78), while the count of one-time partners was highest in San Francisco (11.7/year) and lowest in Detroit (1.5/year). Adjusting for individual PrEP use and demographics, community PrEP coverage correlated with total degree [adjusted incidence rate ratio (aIRR) = 1.73; 95% credible interval (CrI), 0.92–3.44], casual degree (aIRR = 2.05; 95% CrI, 0.90–5.07), and count of one-time partnerships (aIRR = 1.90; 95% CrI, 0.46–8.54). Without adjustment for individual PrEP use, these associations strengthened. There were weaker or no associations with consistent condom use in one-time partnerships (aIRR = 1.68; 95% CrI, 0.86–3.35), main degree (aIRR = 1.21; 95% CrI, 0.48–3.20), and frequency of casual partnership condomless anal sex (aIRR = 0.23; 95% CrI, 0.01–3.60). Conclusion: Most correlations between community PrEP coverage and sexual behavior were explained by individual PrEP use. However, some residual associations remained after controlling for individual PrEP use, suggesting that PrEP coverage may partially drive community-level differences in sexual behaviors.